Diagnostic Utility of Bone Marrow Biopsy/ Bone Marrow Culture in Pyrexia of Unknown Origin: A Ten-Year Retrospective Analysis - Khaliq, Sehar; Ali, Haider (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: This study was carried out to assess the diagnostic utility of BMB and BMC in patients with PUO. Methodology: This retrospective cross-sectional study was conducted at Fauji Foundation Hospital, Rawalpindi. The clinical, laboratory and radiological records from January 2012 - December 2021 were retrieved from our hospital management information system for this study. Data from 63 patients with PUO were analyzed according to Petersdorf criteria. Results: Out of 63 patients with PUO, BMB was diagnostic in 25 (39.68%) patients. The leading cause of PUO was infectious disorders (mycobacterium tuberculosis, visceral leishmaniasis, malaria), followed by inflammatory disorders and hematological malignancies. In 38 (60.31%) patients, BMB could not detect any underlying pathology. BMC showed growth in only 03(4.76%) patients, and the diagnostic yield of BMC was meagre. Conclusion: BMB is essential in establishing a diagnosis in patients with PUO. Infectious diseases are the leading cause of PUO, and BMC should not be included as a routine investigation in the initial evaluation of a patient with PUO.